Emergency Rescue Lobectomy in A Two-Month-Old with Congenital Pulmonary Airway Malformation - Khatavkar, Sonal; Badam, Brinda (Journal of Neonatal Surgery, 2025)
Congenital Pulmonary Airway Malformation (CPAM) is a rare developmental anomaly of the lung that can cause severe respiratory distress in infants. Type I CPAM, characterized by large cystic lesions, may result in life-threatening complications such as pneumothorax and mediastinal shift. We report the case of a two-month-old male infant presenting with respiratory distress due to Type I CPAM involving the right upper and middle lobes. Imaging revealed large cystic lesions with a right-sided pneumothorax and mediastinal shift. During admission the infant developed bradycardia and desaturation, requiring cardiopulmonary resuscitation and intubation, after stabilizing further evaluation and investigation patient was posted for emergency thoracotomy and lobectomy , which were successfully performed. Postoperatively, the infant was managed in the Paediatric Intensive Care Unit with ventilatory support. Early recognition and urgent surgical intervention are critical in symptomatic CPAM cases. Multidisciplinary management is essential for optimizing outcomes in critically ill infants.